Validitas dan Keefektifan E-LKPD Berbasis Guided Inquiry pada Materi Sistem Peredaran Darah untuk Melatihkan Keterampilan Berpikir Kritis Peserta Didik SMA : (Validity and Effectiveness of Guided Inquiry Based E-Worksheet on the Circulatory System to Train Senior High School Students’ Critical Thinking Skills) - Kartikaningtyas, Wahyu; Kuswanti, Nur (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2026)
Kurikulum Merdeka emphasizes the mastery of 21st-century competencies (4C), one of which is critical thinking skills. However, students’ critical thinking skills remain relatively low, as reflected by the decline in the PISA score from 396 in 2018 to 375 in 2022. Critical thinking skills are essential abilities that need to be trained so that students are able to analyze information, evaluate arguments, and solve biological problems logically. The development of digital learning media in the form of Guided Inquiry based electronic student worksheets (E-Worksheet) serves as an alternative to train these skills through the stages of Guided Inquiry. The circulatory system topic was selected because it includes various important concepts that tend to be taught theoretically and are not fully supported by practical activities. This study aims to examine the validity an effectiveness of Guided Inquiry based E-Worksheets in training students’ critical thinking skills. The study employed the ADDIE development model, which consists of the analysis, design, development, implementation, and evaluation stages, involving 30 eleventh grade senior high school students as research subjects. Data were collected through expert validation and critical thinking skills tests. The E-Worksheets were considered valid and effective if each aspect achieved a minimum percentage of 75%. The results showed that the E-Worksheets obtained an average validity score of 100% (very valid), and critical thinking skills achievement of 92.61% (very effective). Based on these reslult, the Guided Inquiry based E-Worksheets is concluded to be valid and effective in training students’ critical thinking skills. Abstrak. Kurikulum Merdeka menekankan penguasaan kompetensi abad ke-21 (4C), salah satunya keterampilan berpikir kritis. Namun, keterampilan berpikir kritis peserta didik masih tergolong rendah, yang tercermin dari penurunan skor PISA tahun 2022 sebesar 375 dibandingkan tahun 2018 sebesar 396. Keterampilan berpikir kritis merupakan kemampuan penting yang perlu dilatihkan agar peserta didik mampu menganalisis informasi, mengevaluasi argumen, serta menyelesaikan permasalahan biologis secara logis. Pengembangan media pembelajaran digital berupa E-LKPD berbasis Guided Inquiry menjadi alternatif untuk melatihkan keterampilan tersebut melalui tahapan Guided Inquiry. Materi sistem peredaran darah dipilih karena mencakup berbagai konsep penting yang selama ini cenderung diajarkan secara teoritis dan belum seluruhnya didukung oleh kegiatan praktikum. Penelitian ini bertujuan mengetahui kevalidan dan keefektifan E-LKPD berbasis Guided Inquiry untuk melatihkan keterampilan berpikir kritis peserta didik. Penelitian menggunakan model ADDIE yang meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi dengan subjek uji coba sebanyak 30 peserta didik kelas XI SMA. Teknik pengumpulan data meliputi validasi ahli dan tes keterampilan berpikir kritis. E-LKPD dinyatakan valid dan efektif apabila masing-masing memperoleh sebesar ≥ 75%. Hasil penelitian menunjukkan bahwa E-LKPD memperoleh nilai rata-rata validitas 100% (sangat valid), dan ketercapaian indikator keterampilan berpikir kritis sebesar 92,61% (sangat efektif). Berdasarkan hasil tersebut, E-LKPD berbasis Guided Inquiry dinyatakan valid dan efektif untuk melatihkan keterampilan berpikir kritis peserta didik.